FAKTOR-FAKTOR YANG MEMPENGARUHI PROFIT DISTRIBUTION MANAGEMENT PADA BANK SYARIAH DI INDONESIA PERIODE 2012-2015 - Ziyadatur Rohmah; Abdul Wahid Mahsuni; Junaidi Junaidi (Universitas Islam Malang, 2017)
The study aimed to determine the effect of CAR (Capital Adequacy Ratio), EDP (Effectiveness of Depositors Funds), AC (Assets Composition), DEP (Depositors), PAM (Productive Assets Management) trough PDM (Profit Distribution Management) for sharia public bank in Indonesia period 2012-2015.the population in this study is sharia public bank with consist 11 banks, meanwhile the sample of the study is consist 6 banks. There were Bank Central Asia Syariah (BCA), Bank Syariah Mandiri (BSM), Bank Rakyat Indonesia Syariah (BRIS), Bank Mega Syariah (BMS), Bank BNI Syariah, and Bank Maybank Syariah. The process of the sampling used purposive sampling. the research method is descriptive statistic, and the assumption is classis. The data analysis used financial report of triwulan in sharia public bank period 2012-2015. Testing in this study used the normality test with multiple linear regression analysis. The result of this study shows that there is effect simultaneously between CAR, EDP, AC, DEP, PAM to Profit Distribution Management. While CAR, AC and PAM were not significant parsial to Profit Distribution Management on sharia public bank in Indonesia period 2012-2015.